2018
DOI: 10.1038/nrd.2018.148
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T cells in the treatment of disease

Abstract: | Regulatory T (T reg) cells suppress inflammation and regulate immune system activity. In patients with systemic or organ-specific autoimmune diseases or those receiving transplanted organs, T reg cells are compromised. Approaches to strengthen T reg cell function, either by expanding them ex vivo and reinfusing them or by increasing the number or capacity of existing T reg cells, have entered clinical trials. Unlike the situation in autoimmunity, in patients with cancer, T reg cells limit the antitumour immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
212
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 252 publications
(216 citation statements)
references
References 320 publications
(334 reference statements)
1
212
2
1
Order By: Relevance
“…Beside Treg reprogramming, Treg cell depletion strategies have also been tested as anticancer therapy . In detail, monoclonal antibodies against CD25 have been used to kill Treg cells by antibody‐dependent cell‐mediated cytotoxicity and complement‐mediated cytotoxicity in preclinical and clinical studies alone and in combination with dendritic cell vaccines .…”
Section: Introductionmentioning
confidence: 99%
“…Beside Treg reprogramming, Treg cell depletion strategies have also been tested as anticancer therapy . In detail, monoclonal antibodies against CD25 have been used to kill Treg cells by antibody‐dependent cell‐mediated cytotoxicity and complement‐mediated cytotoxicity in preclinical and clinical studies alone and in combination with dendritic cell vaccines .…”
Section: Introductionmentioning
confidence: 99%
“…Crohn's disease is mainly characterized by an enhanced Th1 response together with an increased Th17 immune response, which plays a critical role in the pathogenesis of CD . Local immune balance of intestinal tissue is maintained by regulatory T cells (Tregs) in the intestine that inhibit the proliferation and response of other helper‐T cells (Th cells) . Studies have indicated that CD is associated with impaired Treg responses and enhanced Th1/Th17 responses .…”
Section: Introductionmentioning
confidence: 99%
“…These findings encourage to further evaluate circulating Tregs as a potential biomarker for treatment response. Furthermore, alternative therapeutic approaches modulating T‐cell metabolism, such as metformin, may improve the number and functions of Tregs, as showen in other clinical and pre‐clinical models of autoimmune diseases …”
Section: Discussionmentioning
confidence: 99%